Plantar pain is not always fasciitis - N. Romano; A. Fischetti; V. Prono; S. Migone; F. Barbieri; C. Pizzorni; G. Garlaschi; M.A. Cimmino (PAGEPress Publications, 2017)
The case is described of a patient with chronic plantar pain, diagnosed as fasciitis, which was not improved by conventional treatment. Magnetic resonance imaging revealed flexor hallucis longus tenosynovitis, which improved after local glucocorticoid injection.